2009
DOI: 10.2165/11317560-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Incremental 1-Year Medical Resource Utilization and Costs for Patients with Herpes Zoster from a Set of US Health Plans

Abstract: The medical RU and cost data were obtained from the MarketScan Research Database for the years 1998-2003. This database contains inpatient, outpatient and prescription drug data for approximately 14 million individuals of all ages, covered under a variety of fee-for-service and capitated provider reimbursement arrangements, including those with Medicare and private insurance. The work loss estimates were based on the MarketScan Health and Productivity Management Database. Claims for services incurred between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 38 publications
3
66
2
Order By: Relevance
“…[8][9][10][11][12] The cost of treatment, especially of PHN is also very significant. 13 For these reasons, HZ and its complications are a serious public health problem, causing a significant health and economic burden, and a significant loss of quality of life due to the pain caused by the disease and its complications. 12,13 There is considerable information in Spain on the incidence of HZ that comes from population-based epidemiologic studies , and angela Domínguez…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] The cost of treatment, especially of PHN is also very significant. 13 For these reasons, HZ and its complications are a serious public health problem, causing a significant health and economic burden, and a significant loss of quality of life due to the pain caused by the disease and its complications. 12,13 There is considerable information in Spain on the incidence of HZ that comes from population-based epidemiologic studies , and angela Domínguez…”
Section: Introductionmentioning
confidence: 99%
“…White et al (7) attributed costs to HZ using regression analyses based on all services received by patients, with the incremental cost estimate reflecting the difference between HZ and control patients. Dworkin et al (12) used a similar methodology.…”
Section: Discussionmentioning
confidence: 99%
“…This period was selected because it provides cost information without introducing ''noise'' related to medical resource utilization for nonYHZ-related care during the longer follow-up period. Previous research has shown that the majority of HZ-related costs are incurred during this earlier time period (7,11). The current study adapted the medication list used in the Insinga et al to include new classes of drugs and new entries within existing drug classes that may be used in the management of HZ (8).…”
Section: Variable Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2004 study, the economic burden of cutaneous herpes simplex and herpes zoster infections together was estimated at $1.7 billion annually in the United States. 55 Herpes zoster 91 Herpes genitalis infections account for more than $200 million of this total, 92 so the annual economic burden of other cutaneous herpes infections, including herpes labialis, may be extrapolated to be nearly $500 million annually. These values represent rough estimates based on separate analyses and so must be interpreted carefully.…”
Section: Cost Of Treatmentmentioning
confidence: 99%